2012
DOI: 10.1111/j.1600-051x.2012.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans serotypes, the JP2 clone and cytolethal distending toxin genes in a Thai population

Abstract: Our results confirm the previous findings that genotype distribution of A. actinomycetemcomitans varies between ethnic groups. However, no clear relationship between a specific genotype and periodontal conditions was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Currently, six A. actinomycetemcomitans serotypes (a-f) are recognized based on the antigenicity of the O-polysaccharide component of the lipopolysaccharide (LPS) (Page et al 1991, Gmur et al 1993, Kaplan et al 2001. Serotypes a, b and c are the most frequent in Caucasians, Asians, Africans and Latin-Americans, being serotype b the most frequently associated with periodontitis (Chen et al 2010, van der Reijden et al 2010, Roman-Torres et al 2010, Sakellari et al 2011, Aberg et al 2012, Bandhaya et al 2012, Cortelli et al 2012, Jentsch et al 2012.…”
mentioning
confidence: 99%
“…Currently, six A. actinomycetemcomitans serotypes (a-f) are recognized based on the antigenicity of the O-polysaccharide component of the lipopolysaccharide (LPS) (Page et al 1991, Gmur et al 1993, Kaplan et al 2001. Serotypes a, b and c are the most frequent in Caucasians, Asians, Africans and Latin-Americans, being serotype b the most frequently associated with periodontitis (Chen et al 2010, van der Reijden et al 2010, Roman-Torres et al 2010, Sakellari et al 2011, Aberg et al 2012, Bandhaya et al 2012, Cortelli et al 2012, Jentsch et al 2012.…”
mentioning
confidence: 99%
“…While there are 6 serotypes of A. actinomycetemcomitans, serotypes a, b, and c have been isolated the most often from periodontal disease sites (12,14,15). The host response to A. actinomycetemcomitans is the strongest against serotype b strains when the responses against serotype a, b, and c strains in the United States are compared (16).…”
mentioning
confidence: 99%
“…In both studies serotypes c was the dominant serotype, while serotype b was relatively rare (26,27). For 86 A. actinomycetemcomitans strains in Thai adults with varying degrees of periodontal disease severity the serotype c was the dominant serotype, followed by serotypes a (33%) and b (7%) (34), whereas in Korean patients, the serotype distribution was different, the serotypes detected most frequently were c (61.9%) and d (19.0%) (30). The differences between the results from these Asian populations shows that serotype distribution patterns may be affected by geographic variations, even between subjects of the same race/ethnicity.…”
Section: Discussionmentioning
confidence: 96%
“…The studies showed that Asian populations were commonly colonized with A. actinomycetemcomitans serotype c, but were occasionally infected with serotype b (26,27,30,34). Two studies have examined the serotype distribution patterns of A. actinomycetemcomitans in a Japanese population.…”
Section: Discussionmentioning
confidence: 99%